Banks total factor productivity change in a developing economy: does ownership and origins matter? - Sufian, Fadzlan (Elsevier, 2011)
This paper employs the Malmquist Productivity Index (MPI) method to analyze the productivity of the Malaysian banking sector during the period 1995–2004. The empirical findings indicate that the Malaysian banking sector has exhibited productivity regress due to technological regress rather than efficiency decline. We find that the foreign banks have exhibited productivity regress, while their domestic peers have exhibited a marginal productivity increase. During the period under study, productivity levels seems to be positively associated with the stock exchange listed banks, but is negatively related to foreign ownership. In essence, the findings provide support to the home field advantage and the ‘‘limited form’’ of the global advantage hypotheses. On the other hand, the empirical findings seem to reject the ‘liability of unfamiliarness’ hypothesis.